Social Media Marketing in Ukraine during wartime - Dolenko, Arina; Escobar Rios, Andrea; Bahles, Michael; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This diploma thesis aims to determine the effects of the war on Social Media Marketing in the context of Ukraine, with the objective to enhance the effectiveness of existing social media marketing strategies and assist organizations in maintaining a formidable competitive position during the crisis. The theoretical part of this work defines concepts of social media and social media marketing, explores the differences between these definitions, and determines their main functions. Furthermore, this part includes an analysis of the role of social media marketing in crisis management. The practical part, among other things, includes an analysis of the current situation of SMM in Ukraine in terms of challenges created by wartime conditions. It, also, proposes recommendations with social media marketing opportunities that organizations can leverage to maintain their competitive position.
Vedoucí práce: Andrea Escobar Rios
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses